Pulley ring suture increases shoulder stability after biceps tendon transposition - Zhang, Duzheng; Wu, Jiezhou; Zhang, Liyun; Chen, Qiyun; Wang, Chao; Cai, Ming; Cong, Ruijun (Frontiers in Surgery, 2025)
ObjectiveModified double-row biceps tenodesis (MDBT) has been proved to be effective in treating slap injuries, but the impact of closing the rotator cuff gap remained postoperatively (the Pulley ring repair) on the long-term shoulder function and stability has not been conclusively investigated.MethodsA retrospective study was conducted on 157 patients with isolated unilateral type II SLAP lesions treated with MDBT from January 2019 to January 2023. 77 patients were without the Pulley ring repair (group A) and the remaining 80 patients were with the Pulley ring repair (group B). T-test, Anova, and chi-square analyses were used to compare the two groups for any statistical differences in the 37 variables. Lasso regression was used to screen and analyze the variables, assess risk, and construct a predictive assessment model.ResultsThere were significant differences between the two groups at 1 year in ASES and UCLA score (p < 0.01). Risk factors screened by LASSO regression were five including Grouping information, Mean T value of bone mineral density, and 3 Months post operation's UCLA score. These statistically significant variables and their coefficients were used to build a generalized linear equation and selected to build the final model including Grouping information (OR:1.61E + 01;95% CI:5.8854–52.5200), Mean T value of bone mineral density (OR:6.95E + 00;95% CI:2.4695–25.6797) and 3 Months post operation UCLA score (OR:1.77E + 00;95% CI:1.4810–2.2539).ConclusionsCompared with the traditional MDBT, the modified MDBT is more effective in improving the long-term function of the glenohumeral joint and better restoring the biological state of the glenohumeral joint.